Effectiveness of use of Electronic Module in Sociology Subjects of Social Change for Equality Education Package C - Hariyani, Mutia; Kusumawardani, Dwi; Sukardjo, Moch (Journal of Education Technology, 2021)
Electronic modules have an important role because they can help the learning process of students. The problems obtained can be seen from the motivation and learning outcomes that cannot be said to be optimal, one of the causes is the lack of learning media used. With the use of electronic modules, abstract material can be concreted and make students interested and motivated in learning and can improve learning outcomes. The purpose of this study was to test the effectiveness of the electronic module on cognitive learning outcomes on social change material in the Education package C program. The research approach used was a quantitative approach. The type of research used is Pre-Experimental. The design used in this research is One Group Pretest-Posttest. The research subjects were students of class XII package C program, totaling 38 students with 17 males and 21 females. Methods of data collection by observation, interviews, and tests. The instrumentes used are in the form of an objective test with a total of 10 items. The analysis of improving learning outcomes was analyzed using the N-Gain formula. N-Gain is used to calculate the increase in learning outcomes. Based on the N-gain analysis, student learning outcomes show a value of 0.60 in the medium category and the value of the effectiveness of N-gain in percent is 60 with an effective enough category. So learning by using electronic modules can improve student learning outcomes.